Effects Of Locally-Made Probiotics on Drinking Water on the Performance of Chickens - Analyn Cinco Moniño; Roger Yatan Ibañez Jr.; Primitivo Diaz Moniño Jr. (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
This study investigated the effects of locally-made probiotics on the performance of Kabir and Starbro broilers. The birds were randomly assigned to four treatments, and their body weight, weight development, feed consumption, feed conversion efficiency, dressing percentage, livability rates, and income over feed and chick cost were measured. The results showed a significant interaction between the breed of chicken and the type of probiotics after 21 days of feeding in terms of body weight, body weight gain, feed consumption, and feed conversion efficiency. However, no significant interaction was observed at 35 days of feeding. The use of locally produced probiotics in drinking water improved the dressing percentage of both breeds of chicken, overall body weight gain, and overall feed consumption compared to the control group. Livability rates were not significantly affected by the inclusion of different locally-made probiotics in drinking water. Net income per chicken was marginally higher for the chickens fed with locally produced probiotics. Further studies are recommended to assess the benefits of locally-produced probiotics in laying chicken and other types of livestock and poultry. These findings provide insights into the potential application of locally-made probiotics as an alternative to commercial products for improving chicken performance.